Demokrasi Deliberatif dalam Praktik Musyawarah Kalurahan: Studi Kasus Musyawarah Kalurahan Guwosari Tahun 2025 - Mochamad Bilal Tri Andika; Moh. Ilyas Rolis (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the dynamics of deliberative democracy in the practice of Musyawarah Kalurahan (Muskal) in Guwosari Village, Pajangan Sub-district, Bantul Regency. Muskal is positioned as a deliberative public sphere that enables citizens to directly participate in the process of village-level policy formulation. This research employs a descriptive qualitative method with a case study approach. Data were collected through observation of Muskal sessions, interviews with the Chairperson of the Village Consultative Body (Bamuskal), official documentation, and a literature review. Data analysis was conducted using Miles and Huberman’s interactive model, supported by methodological triangulation to ensure data credibility. The findings indicate that, procedurally, Muskal in Guwosari Village reflects key principles of deliberative democracy, particularly inclusiveness and openness in citizen participation. Innovations in participant selection mechanisms and the involvement of citizens directly affected by Village-Owned Enterprise (BUMKal) policies demonstrate efforts to create a more substantive deliberative space. However, at a substantive level, the deliberative process still faces significant limitations, especially the weak presence of critical dialogue and two-way communication between citizens and formal actors. Consequently, Muskal tends to function more as a forum for information dissemination rather than as an active arena of deliberative discourse. This study concludes that the practice of deliberative democracy in Guwosari Village is in a transitional phase structurally progressive yet not fully mature in discursive terms. Therefore, strengthening citizens’ deliberative capacities, facilitating public communication, and cultivating a critical and participatory deliberative culture are necessary to enable Muskal to function as a more substantive and sustainable democratic public sphere.